DISTRIBUTION AND SIGNIFICANCE OF HEAVY METALS IN SOME COALS FROM BENUE TROUGH - Usman, F.; Dangoggo, S. M.; Muhammad, A. B.; Umar, K. J.; Shuaibu, I.; Hamza, A.; Abubakar, I.; Bello, Y. K. (FUDMA JOURNAL OF SCIENCES, 2023)
The knowledge of the concentration of heavy metals is required when evaluating coals for combustion, conversion and also to evaluate potential undesirable environmental and health impacts resulting from coal use and their geochemical relevance. This research focus on determination of concentrations of Cr,Fe, Cd, Pb, Mn, Zn and Cu in Chikila, Lamja, Lafia Obi, Maiganga and Okaba coals from Benue Trough using Atomic Absorption Spectrophotometry (AAS). Lafia Obi coal has the highest concentrations of Fe, Cr and Mn with values 314.28 mg/kg, 108.60 mg/kg and 103.53 mg/kg respectively. The highest concentrations of Cu (89.23 mg/kg) and Zn (8.17 mg/kg) were found in Okaba coal while Lamja coal has the highest concentration of Cd (1.28 mg/kg). Lead was below the detection limit in all the coal samples while chromium was not detected in Lamja coal only. The concentrations of all the metals in the coal samples, with the exception of cadmium in Chikila coal, are above the approved limits set by the Federal Environmental Protection Agency. Therefore, inappropriate combustion of these coals and the wastes generated may pose a threat to the immediate environment. All the coals investigated are of similar depositional environment